Pengaruh Artificial Intelligence (AI) terhadap Efektivitas Proses Pembelajaran di Era Digital - Pendiasari, Ni Luh Candy (CV. Lenggogeni Data Publishing, 2026)
This systematic literature review (SLR) analyzes the influence of Artificial Intelligence (AI) on learning effectiveness in the digital era by reviewing 33 key academic references. Utilizing the PRISMA protocol, this study synthesizes findings regarding cognitive impacts, student engagement, and the ethical challenges of AI integration in education. Meta-analysis results indicate an overall effect size of , with Generative AI and chatbot technologies achieving the highest performance at . In Indonesia, AI implementation has significantly improved students' critical thinking skills, raising average scores from 47.13 to 75.96. However, the study reveals a